Role and responsibilities of a forensic mental health nurse: a scoping review protocol - Helen Walker; Eileen Harkess-Murphy; Robin Ion; Joshua Cheyne; Lindsay Tulloch; Marie McCaig (BMJ Open, 2025)
Introduction Forensic mental health nursing (FMHN) is a subspeciality of psychiatric nursing. An area of mental health nursing care that is situated at the intersection of health, social and criminal justice systems. Over the past two decades, FMHN has evolved beyond custodial and containment practice. Contemporary FMHN has an emphasis on therapeutic interventions, identifying patients as partners in care and nursed through a trauma-informed, recovery-orientated lens. Numerous scholars have examined the role of the FMHN and its inherent complexities. However, much of the existing literature is outdated and is limited in scope, describing the role and responsibilities of an FMHN relevant to contemporary practice. This paper maps the literature over the last 20 years to establish what explicitly defines the modern FMHN, specifically examining factors that have shaped the role and influenced patient outcomes and care delivery; including areas of good practice.Methods and analysis In line with the Joanna Briggs Institute (JBI) guidance on scoping reviews, including Arksey and O’Malley’s (2005) five-step framework, we will conduct a search within MEDLINE (EBSCO), CINAHL (EBSCO), PsycINFO (Ovid) and the Cochrane Database of Systematic Reviews and Cochrane Central Register of Controlled Trials in the Cochrane Library. The first author conducted a preliminary search in October 2024 to identify literature in this area and a review of keywords to develop the foundation search strategy. The search strategy was constructed in the MEDLINE (EBSCO) database May 2025 by the lead author and an information specialist/librarian. Eligibility criteria of publications written in English, with a date range of 2004–2024, including the first quarter of 2025, forensic mental health nurse population and secure inpatient settings. All extracted literature will be exported into EndNote V.21 in order to support the removal of duplicates and assist in the screening and selection process. A two-step data selection process will include stage one, where two authors independently conduct a preliminary title and abstract screen of all extracted data using a data extraction instrument developed per JBI scoping review guidance. Each paper will be categorised as ‘yes’, ‘no’ or ‘maybe’. Step two: All documents categorised as ‘yes’ or ‘maybe’ will undergo a full-text screening. Narrative summaries and tables will present the results in full.Ethics and dissemination This scoping review will analyse existing published data; therefore, ethical approval is not required. The findings of this review will be presented at local and international conferences and published in peer-reviewed journals. The formal search will commence in June 2025, with an aim to submit in full for peer-review publication by October 2025.